Aplikasi Media Pembelajaran pada Kelas 4 Tema 8 Subtema 3 Bangga Terhadap Daerah Tempat Tinggalku di MIN 2 Kebonagung Imogiri Bantul, Yogyakarta - Rizki Maulinisa; Aprinaldo Anrada (Al-Riwayah : Jurnal Kependidikan, 2021)
The learning media used in the process of learning Theme 8 Subtema 3 Proud of the Region where I live in grade 4 at MIN 2 Kebon Agung Imogiri Bantul is internet and projector media. This media is very commonly used by teachers. In its learning activities the media is used to convey material about various production and professional activities that exist around students through pictures and videos. The obstacle in the learning media application is that teachers have difficulty in determining the media used because not all material can use interesting media. This is also due to the teacher's limitations in mastering learning media. But in the learning process, many students have understood the material by using learning media. Apart from all that, there are still students who do not understand the material because the teacher does not pay attention to all student activities in class. Many students play during learning. Classroom learning begins with showing pictures and videos related to the material to be explained, then the teacher will provide stimulus questions to students. The problem is that teachers have difficulty choosing a fixed learning media, this is also related to the teacher's limitations in mastering learning media